Pelatihan Karyawan Pada CV. Arsana Sentosa - Aniqa Asriah; Syafira Adinda Fauzy; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this industrial visit is to find out about employee training and development at CV. Arsana Sentosa which is an important thing to do for CV. Arsana Sentosa, this visit is very important in a visit or scientific article. relevant past visits serve to organize theory and benefits in training among employees. This article discusses knowledge, skills and attitudes about a Human Resource Management relationship that has a goal in training. The purpose of this article is to develop and find innovative training in the future by carrying out training objectives by means of knowledge, skills and attitudes that are honest and good. Articles from the Visit include: The first three are